2020
DOI: 10.3390/ph13100303
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia bentzoë, a Mascarene Endemic Plant, Inhibits Human Hepatocellular Carcinoma Cells Growth In Vitro via G0/G1 Phase Cell Cycle Arrest

Abstract: Tropical forests constitute a prolific sanctuary of unique floral diversity and potential medicinal sources, however, many of them remain unexplored. The scarcity of rigorous scientific data on the surviving Mascarene endemic taxa renders bioprospecting of this untapped resource of utmost importance. Thus, in view of valorizing the native resource, this study has as its objective to investigate the bioactivities of endemic leaf extracts. Herein, seven Mascarene endemic plants leaves were extracted and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 78 publications
2
16
0
Order By: Relevance
“…Following trial experiments using different dilutions of extract from 10 μg/mL to 40 μg/mL at 24 hours and 48 hours, the cells were exposed to 10 μg/mL extract for 24 hours. The negative control consisted of untreated HepG2 cells while the positive control cells were treated with 200 μM H 2 O 2 for 30 minutes as previously reported [21]. Cells were washed with PBS, harvested using 1 X trypsin-EDTA and re-suspended in 100 μL of PBS.…”
Section: Cell Culturementioning
confidence: 99%
“…Following trial experiments using different dilutions of extract from 10 μg/mL to 40 μg/mL at 24 hours and 48 hours, the cells were exposed to 10 μg/mL extract for 24 hours. The negative control consisted of untreated HepG2 cells while the positive control cells were treated with 200 μM H 2 O 2 for 30 minutes as previously reported [21]. Cells were washed with PBS, harvested using 1 X trypsin-EDTA and re-suspended in 100 μL of PBS.…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, worldwide 28.000 plant taxa have been reported to have medicinal properties. It has been recorded that more than 3000 species have ethnomedical applications against many diseases including cancer [2]. According to recent studies, the use of endemic and medicinal plants in the food, pharmaceutical and cosmetic industries is recently increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 28,000 known plant taxa have been reported worldwide to have medicinal values. It has been reported that more than 3000 species have ethnomedical usage and applications against many diseases including cancer and diabetes mellitus [ 1 ]. However, herbal and medicinal plants play crucial role in the development of modern medicine and healthcare because they cause milder adverse health effects than conventional medicines and drugs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%